Measurement of television white space spectrum in the Central region of Ghana - Quansah, Daniel Kwame Kwansah (2021)
A thesis submitted to the Department of Computer Science, College of Science, in partial fulfilment of the requirements for the degree of Master of Philosophy in Information Technology